FICTIVE MOTION IN ENGLISH AND SPANISH - Rojo, Ana; Valenzuela, Javier (International Journal of English Studies, 2003)
This paper analyzes fictive motion expressions in English and Spanish with the twofold aim of (a) finding out whether the differences that have been reported in the expression of motion in English and Spanish also apply to fictive motion, and (b) checking whether the similarities and differences reported by Matsumoto for English and Japanese also apply to English and Spanish. We start by offering a detailed account of the similarities and differences between the expression of motion in English and Spanish; subsequently, we take a closer look at fictive motion expressions in English and Japanese. We then present two different studies carried out with the aim of gathering additional data on Spanish fictive motion expressions. The first study focuses on the strategies used by translators in rendering fictive motion expressions from English into Spanish. The second experiment analyses a Corpus of expressions generated using elicitation from drawings. The paper concludes with a discussion of the findings and directions of future research.